Safety and Effectiveness of the Titanium mAXIS Stapes Prosthesis: Multicentric Short-Term Outcome - Beutner, Dirk; Bevis, Nicholas; Loader, Benjamin; Windisch, Franz; Arndt, Susan; Offergeld, Christian; Wolfram, Wendelin; Niederwanger, Lisa; Zwittag, Paul Martin; Rubicz, Nina; Schimanski, Esther; Arnoldner, Christoph; et al. (Otology & Neurotology, 2025)
Objective Otosclerosis leads to ossification of the stapes footplate and is responsible for a significant number of patients having hearing loss. Stapes surgery is a treatment for otosclerosis with excellent postoperative hearing outcomes. The aim of this retrospective study was to analyze the safety and effectiveness of the titanium mAXIS prosthesis in a multicentric setting. Methods Ninety-four surgeries with implantation of the mAXIS stapes prosthesis took place in a multicenter study group. During follow-up at 59 (±48.1) days, pure-tone audiometry was performed. The pure-tone averages of 0.5, 1, 2, and 3 kHz (PTA-4) were determined. Results No device-related adverse events were reported. There were 88 patients who reported for follow-up, at which pure-tone audiometry was performed. The PTA-4 air-bone gap (ABG) at follow-up was 8.8 (±6.0) dB. In 64.8% of the patients, the postoperative PTA-4 ABG was within 10 dB and in 94.3% it was within 20 dB. The postoperative PTA-4 thresholds for bone conduction were stable in 95.5% of cases. Conclusion The results of this multicentric study demonstrate the safety of the mAXIS titanium stapes prosthesis. The prosthesis shows promising audiological outcomes. Future studies are needed to assess long-term efficacy.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Middle ear prosthesis; Otosclerosis; Stapedotomy; Stapes prosthesis; Stapes surgery